DIGITAL TECHNOLOGY Opportunities and barriers for usage of personal health records in hospital – report from a workshop of the Health Informatics Unit at the Royal College of Physicians. (2019) - Subbe, Christian P; Øvretveit, John; Quinn, Nicola; Wyatt, Jeremy C
No abstract available